2008
DOI: 10.1055/s-2008-1038620
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Tolerance while Running: Effect of Repeated Trials

Abstract: This study assessed tolerance to fluid ingestion with repeated sessions of drinking while running. Runners (n = 7; age 22 +/- 2 yr; V O (2max) = 54.4 +/- 7.1 ml/kg/min) performed six 90-min runs (65 % V O (2max); separated by 7 - 11 days). During run 1, subjects drank a glucose-electrolyte solution AD LIBITUM for 1 min every 10 min. During runs 2 - 6, subjects drank a volume of the solution every 10 min equal to their sweat production over 10 min during run 1. Stomach comfort (1 - 4 scale) and gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…23 Although it is simple, the alteration of body mass after physical exercise has been considered a suitable parameter to assess dehydration. 24 The body mass variation found in this study was similar other studies. 2,25 The body mass reduction is associated with the decrease in the hydric body content, mainly for the maintenance of the temperature to avoid damaging the normal physiologic functions.…”
Section: Discussionsupporting
confidence: 92%
“…23 Although it is simple, the alteration of body mass after physical exercise has been considered a suitable parameter to assess dehydration. 24 The body mass variation found in this study was similar other studies. 2,25 The body mass reduction is associated with the decrease in the hydric body content, mainly for the maintenance of the temperature to avoid damaging the normal physiologic functions.…”
Section: Discussionsupporting
confidence: 92%
“…For example, it has previously been observed that acute episodes of substantially high intragastric pressure and intestinal load attenuates gastric emptying and orocaecal transit time through neural and hormonal feedback mechanisms along the gastrointestinal tract (Costill and Saltin 1974;(Miller et al 1981;Minami and McCallum 1984). However, repeated ingestion of a test solution has been shown to maintain a consistent intragastric pressure resulting in an enhanced gastric emptying rate and improved stomach comfort (Lambert et al 2008;Noakes et al 1991). It is, therefore, not surprising that two weeks of gut-training (i.e., repetitive gut-challenge) on CHO-S and CHO-F resulted in marked reductions in gut discomfort and gastrointestinal symptoms in GC2.…”
Section: Blood Glucose Plasma Cortisol and I-fabp Concentrationmentioning
confidence: 99%
“…Lambert et al [50] assessed tolerance to fluid ingestion with repeated sessions of drinking while running. During five runs, subjects drank a volume of the solution every 10 min equal to their sweat production over 10 min.…”
Section: ‘Training the Gut’mentioning
confidence: 99%